2010
DOI: 10.1109/lsp.2009.2036879
|View full text |Cite
|
Sign up to set email alerts
|

Motion Vector Outlier Rejection Cascade for Global Motion Estimation

Abstract: Global motion estimation (GME) from motion vector (MV) field in compressed domain greatly reduces the complexity of conventional pixel-based GME. However, outlier MVs, caused by noise or foreground objects, may reduce the accuracy of MV-based GME. In this paper, we propose a cascade-of-rejectors approach for removing MV outliers to achieve efficient and accurate GME. Experimental results show that the proposed MV outlier rejection cascade significantly lowers the complexity MV-based GME, with an accuracy close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…For block i, a similarity value i S is calculated based on the cosine of the similarity between input motion vector and the one in the smoothed motion vector field, as follows: The similarity of zero motion vectors is set to 0. In this research, 30% of motion vectors were found to be outliers, similarly to the work in [4]. Fig.…”
Section: Motion Vector Outlier Removalsupporting
confidence: 80%
See 4 more Smart Citations
“…For block i, a similarity value i S is calculated based on the cosine of the similarity between input motion vector and the one in the smoothed motion vector field, as follows: The similarity of zero motion vectors is set to 0. In this research, 30% of motion vectors were found to be outliers, similarly to the work in [4]. Fig.…”
Section: Motion Vector Outlier Removalsupporting
confidence: 80%
“…The same four sets of global motion parameters as in [2,4], which are shown in Table 1, are used. The synthetic motion vector fields of these four motion models are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations